An explanatory study on the effect TikTok has on the consumer buying behaviour of Generation Z, within the COVID-19 pandemic. - Sinclair, Tegan (The IIE, 2022)
Over the last three years I have been interested in social media marketing and what businesses can grow with the right strategy. In 2020, I started my own social media marketing business, E-merge Media. I have enjoyed learning about social media platforms and their various marketing tools. This led to my decision to conduct an explanatory study on the effect TikTok has on the consumer buying behaviour of Generation Z, within the COVID-19 pandemic. There is a lack of research regarding TikTok’s effect on the buying behaviour of Generation Z in South Africa. This research report aims to provide insight into whether TikTok leads to buying behaviour. The research methodology took a qualitative approach, using focus groups and an open ended questionnaire. This approach was used to gain insight into the opinions and feelings of Generation Z in relation to TikTok and their buying behaviour. The research concluded that TikTok has an effect on the consumer buying behaviour of Generation Z, within the COVID-19 pandemic. However, this influence is limited in South Africa due to the lack of access to international brands and affordable shipping. The data concluded that TikTok is an effective marketing tool for brands marketing strategies.
Keywords: Customer behaviour; Social media; Digital marketing; Advertising